An unusual case of iatrogenic Twiddler's syndrome. Issue 2 (February 2020) - Sanniti, Aurora; Sergi, Domenico; Barone, Lucy; Magliano, Giulia; Della Rocca, Domenico G.; Tritto, Massimo; Romeo, Francesco
Abstract : N/A: Twiddler's syndrome is an uncommon cause of cardiac implantable electronic device malfunction, usually due to manipulation of the pulse generator. A few spontaneous cases have already been described. We present the unique case of a 77-year-old woman who experienced iatrogenic Twiddler's syndrome.